Oceanographic Data of the 31st Japanese Antarctic Research Expedition from November 1989 to March 1990 - イケダ, シュンイチ; コジマ, テツヤ; Ikeda, Syunichi; Kojima, Tetsuya (National Institute of Polar Research, 1992)
P(論文) departmental bulletin paper